Optimal feedback stabilization of a two-axis gimbaled system subject to saturation nonlinearity and multiple disturbances. (February 2014) - Zhan, ST; Yan, WX; Fu, Z; Zhao, YZ
Disturbances induced from platform motion, gimbal imbalance and state couplings, may severely degrade the line-of-sight tracking accuracy of a two-axis gimbaled system and even induce instability. This article intends to present a stable approach to realize optimal disturbance attenuation for a yaw-pitch gimbaled system, in the presence of saturation nonlinearity and multiple disturbances. A dynamic model of the line-of-sight dynamics is formulated and linearized; feedback controllers are synthesized via linear matrix inequalities and convex optimization; state trajectories of the system before and after stabilization are compared to examine the effectiveness of the feedback approach. The simulation results show that the synthesized controllers are effective in stabilizing the system and realizing optimal disturbance attenuation.